Fractal dimension and cheek teeth crown complexity in the giant rodent Eumegamys paranensis - Candela, Adriana Magdalena (2013)
In this work, we analyse cheek teeth crown complexity through the calculation of fractal dimension in the giant caviomorph rodent Eumegamys paranensis (Late Miocene of Argentina) and evaluate its functional significance. Our results indicate that, in all teeth of Eumegamys paranensis, the fractal dimension was around 1.5, similar to the Koch quadratic curve type two. The anterior portions of the molars, with the highest values of fractal dimension, are interpreted as areas that supported greater occlusal pressures. Crown complexity in E. paranensis is related to the increased mechanical capacity to process relatively demanding food items and to allow more food to be divided in each masticatory cycle. Eumegamys paranensis would have been a mixed feeder, consuming a variable diet obtained close to the ground. This feeding behaviour is compatible with the heterogeneous environment inferred for the Mesopotamic area during the Late Miocene. E. paranensis was probably a wide ranging species, being able to eat close to water bodies and in gallery forests that occurred in the surrounding of the pre-Paraná river system.